1982
DOI: 10.1530/acta.0.1000623
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyposmotic and sodium chloride hyperosmotic environments on the secretion and synthesis of prolactin from human decidua in vitro

Abstract: Using a paired design as well as a cross-over design both with 16 h incubation periods, we have incubated human decidua in hyposmotic, isosmotic, and sodium chloride hyperosmotic media. In the cross-over design each tissue aliquot was subjected to 3 media with different osmolalities, one of which was isosmotic. Thus, intensive utilization of the tissue was possible. The results of the cross-over study were identical with the result of the paired design. We found a decreased secretion of prolactin in hyposmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…Further, the proportion of living cells found after trypan blue staining is similar that reported earlier (Tomita et al 1982) and we suspect that the main cell death occurs during preparation of the tissue before incubation. In our first report the slightly decreasing glucose consumption and the histolo¬ gical appearance were reported earlier (Andersen et al 1982) and we conclude that almost all the tissue stays alive and metabolically active during the successive incubations.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Further, the proportion of living cells found after trypan blue staining is similar that reported earlier (Tomita et al 1982) and we suspect that the main cell death occurs during preparation of the tissue before incubation. In our first report the slightly decreasing glucose consumption and the histolo¬ gical appearance were reported earlier (Andersen et al 1982) and we conclude that almost all the tissue stays alive and metabolically active during the successive incubations.…”
Section: Discussionsupporting
confidence: 81%
“…A detailed example of analysis of variance using the cross-over design has been given previously (Andersen et al 1982) and in the same way the experiments of this report showed significant flask to flask variation in more than half of the experi¬ ments. Fig.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Although an agreement is far from being reached [Adler et al, 1975;Berl et al, 1976;Epstein et al, 1977;Dearlove, 1981;Bliss and Lote, 1982], several reports have proposed an association between PRL and osmoregula tion, the hormone being osmotically regu lated [Buckman and Peake, 1973;Buckman et al, 1973;Relkin, 1974;Andersen et al, 1982] , or acting on osmotic regulation [Dharmamba et al, 1967;Josimovich et al, 1977;Ensor, 1978;Leontic et al, 1979;Gopalakrishnan et al, 1980;Mor ley et al, 1981]. Since loss of endogenous heat generated by contracting muscles can lead to marked blood fluid shifts [Senay, 1979], we postu lated that prolactinemic changes observed during exercise could be associated with vari ations in core temperature and/or in blood osmolality.…”
Section: Introductionmentioning
confidence: 99%